Carbon Emissions and Economic Growth in Azerbaijan: An Empirical Analysis - Suleymanov, Elchin; Kazimov, Shaig; Safarli, Elnur; Alirzayev, Elvin (International Journal of Energy Economics and Policy, 2025)
The increasing energy consumption and industrial activities that release CO2 emissions into the atmosphere have become one of the most serious environmental issues of today. This article discusses the current status in Azerbaijan regarding the development of effective approaches to reduce carbon emissions and ensure sustainable development, and it proposes relevant strategies for managing the carbon footprint. It aims to develop more efficient policies to control CO2 emissions by studying the relationship between the economy and environment in Azerbaijan. Based on the findings of the econometric model conducted within this research between 1990 and 2023 on Azerbaijan, as the economy grows, per capita CO2 emissions tend to increase, which is due to rising industrial activities, energy consumption, and other economic drivers. A positive long-term relationship between population growth and per capita CO2 emissions depicts higher overall energy usage, increased demand for goods and services, and rising transportation needs. Considering the strong correlation between economic growth and CO2 emissions, it may be premature to assert the validity of the Kuznets curve for Azerbaijani economy as a developing country.